PERAN DAKWAH ANREGURUTTA HAJI MUHAMMAD SANUSI BACO DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN PADA JAMAAH MASJID RAYA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The main problem in this research is How the Role of Da'wah Anregurutta Haji Muhammad Sanusi Baco in increasing religious understanding in Jamaah Masjid Raya Makassar ?. Based on the main problem, it is described into two sub-problems, namely: 1) What da'wah activities did Anregurutta Haji Muhammad Sanusi Baco do in increasing religious understanding of the Jamaah Masjid Raya Makassar? 2) What are the opportunities and challenges for the preaching of Anregurutta Haji Muhammad Sanusi Baco in increasing religious understanding in Jamaah Masjid Raya Makassar? The results showed that the Da'wah Activities of Anregurutta Haji Muhammad Sanusi Baco in Improving Religious Understanding in the Congregation of the Great Mosque of Makassar such as regular recitation, religious lectures (Hikmah Maulid the Great Prophet Muhammad Saw, Friday sermons, Isra 'Mi'raj, and Islamic New Year or Welcoming Muharram Month) and Training of Ulama Cadres. As for the Opportunities for Da'wah Anregurutta Haji Muhammad Sanusi Baco in Improving Religious Understanding of the Congregation of the Great Mosque of Makassar, namely Accepted from Various Circles of Society (Jamaah), the Great Mosque as an Icon of the City of Makassar, Availability of Adequate Facilities and Support from All Levels of Society. Meanwhile, the challenge of Da'wah Anregurutta Haji Muhammad Sanusi Baco in Improving Religious Understanding of the Congregation of the Great Mosque of Makassar is Difference of Opinion and Time Sharing. The implication of this research is that the Makassar Grand Mosque Foundation hopes to increase religious activities for the birth of people who believe and have faith in Allah SWT.